Inhibition of thymidine phosphorylase (PD-ECGF) from SD-lymphoma by phosphonomethoxyalkyl thymines - Votruba, Ivan; Pomeisl, Karel; Tloust'ová, Eva; Holý, Antonín; Otová, Berta (Biochemical pharmacology, 2005)
A series of thymine phosphonomethoxyalkyl derivatives were evaluated for their ability to inhibit thymidine phosphorylase (dThdPase) purified from rat spontaneous T-cell lymphoma. A kinetic study of thymidine phosphorolysis catalyzed by dThdPase was performed with thymidine and/or inorganic phosphate as substrates. Data show that the substantial inhibitory effect of these acyclic nucleotide analogues is decreasing in the order of (R)-FPMPT>(S)-FPMPT>or=(R)-HPMPT>(S)-PMPT>(S)-HPMPT>PMET>or=(R)-PMPT. The inhibitory potency (K(i)/(dThd)K(m)) of the most efficient inhibitors from this series against T-cell lymphoma enzyme is 0.0026 for (R)-FPMPT and 0.0048 for (S)-FPMPT. The studied compounds do not inhibit Escherichia coli and human enzyme and possess lower inhibitory potency against rat liver thymidine phosphorylase.
Keywords: Thymopoietins; stereoizomerie; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; organofosfonáty; thymopoetiny; Thymine; krysa rodu Rattus; thymin; zvířata; Stereoisomerism; Lymphoma, T-Cell; lymfom T-buněčný; Thymidine Phosphorylase; potkani Sprague-Dawley; inhibitory enzymů; Rats; Rats, Sprague-Dawley; Organophosphonates; Animals; thymidinfosforylasa; Enzyme Inhibitors